Distinct mechanisms of hypoglycaemia in patients with somatostatin‐secreting neuroendocrine tumours. Issue 4 (27th June 2019) - Wiesli, Peter; Pavlicek, Vojtech; Brändle, Michael; Pfammatter, Thomas; Perren, Aurel; Schmid, Christoph
Abstract: Introduction: Somatostatin‐secreting neuroendocrine tumours may present with diabetes, cholelithiasis and steatorrhoea. In addition, hypoglycaemia has been associated with somatostatinomas. However, the mechanism of hypoglycaemia in patients with somatostatinomas has not been well characterized. Methods: We describe two patients with recurrent neuroglycopenic episodes caused by somatostatin‐secreting neuroendocrine tumours in the liver, detected by abdominal CTs and whole‐body octreotide scintigraphy scans and confirmed by biopsy. Results: Pancreatic islet hyperplasia and co‐secretion of insulin (in addition to somatostatin) from tumour cells, respectively, have been characterized as completely distinct mechanisms of hypoglycaemia at both the functional and morphological levels in these two patients. Conclusions: Hypoglycaemia may be caused by different mechanisms in patients with somatostatinomas. Abstract : Somatostatin‐secreting tumours may induce hypoglycaemia by distinct mechanisms. Pancreatic islet hyperplasia and co‐secretion of insulin (in addition to somatostatin) from tumour cells, respectively, have been characterized at the functional and morphological level in two patients with malignant somatostatinomas.